Sustainability in Urban Hotels: A Case Study of Mandarin Oriental Jakarta - Tirza Irene Kaunang; Dianne O. Rondonuwu; Benny Irwan Towoliu; Pearl Loesye Wenas (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This research presents qualitative single case study analyzing environmental sustainability practices at Mandarin Oriental Jakarta, a leading 5-star hotel, to address the limited detailed analyses of individual luxury urban Indonesian hotels employing data triangulation through interviews, participatory observations and social media documentation. The result of this research is divided into five crucial dimensions: energy efficiency, water management, waste and recycling management, eco-friendly product usage, and environmental certification. Findings reveal a sophisticated, multi-faceted program demonstrating a strategic blend of foundational efficiency and forward-thinking investments in energy, proactive water resource circularity, and externally validated leadership in waste-to-resource innovation. The hotel also shows commitment to integrated sustainable supply chains and a robust internal governance system actively pursuing top-tier international environmental certifications. This research offers practical insights for hotel policy refinement and significantly enriches academic understanding of the Green Hotel Concept, Sustainable Tourism, and the Green Industry, providing a detailed blueprint for sustainable luxury hospitality in a major metropolitan environment.